A Hybrid Meshing Framework Adapted to the Topography to Simulate Atmospheric Boundary Layer Flows. (March 2022) - Gargallo-Peiró, Abel; Avila, Matias; Folch, Arnau
Abstract: A new topography adapted mesh generation framework tailored to simulate Atmospheric Boundary Layer (ABL) flows on complex terrains is presented. The mesher is fully automatic given: the maximum and minimum surface mesh size, and the mesh size at the top of the ABL. The following contributions to the meshing workflow for ABL flow simulation are performed. First, we present a smooth topography modeling to query first and second-order geometry derivatives. Second, we propose a new adaptive meshing procedure to discretize the topography based on two different metrics. Third, we present the ABL mesher, featuring both prisms and tetrahedra. We extrude the triangles of the adapted surface mesh, generating prisms that reproduce the Surface Boundary Layer. Then, the rest of the domain is meshed with an unstructured tetrahedral mesh. In addition, we detail a hybrid quality optimization approach for both the surface and volume meshers, analyzing its impact on the solver for high-complexity terrains. We analyze the convergence of the triangle adaptive approach, obtaining quadratic convergence to the geometry and reducing to one-half the error for the same amount of degrees of freedom than without adaptivity and optimization. We also study the mesh convergence of our Reynolds-averaged Navier–Stokes (RANS) solver, obtaining quadratic mesh convergence to the solution, and using a 30% of the degrees of freedom while reducing a 20% of the error of standard semi-structured approaches. Finally, we present the generated meshes and the simulation results for a complete complex topographic scenario. Highlights: Topography modeling to query first and second-order derivatives of the geometry. Metric-driven mesh adaptation procedure for topographic scenarios. Hybrid meshing framework for ABL flow simulation on complex topographies. Hybrid optimization framework, detailing the impact on the RANS solver. Analysis of the convergence to the topography geometry and to the solution. Graphical abstract: